OPTIMASI TEMPERATUR INTERFACE PADA PELAPISAN ULANG NI-HARD 1 DENGAN METODE GRAVITY CASTING - Hanaldi, Kus; Purwadi, Wiwik; Kurnia Nurzaenal, Friya (Jurnal Teknologi Terapan, 2017)
Grinding roll is one type of product made by the method of bimetallic casting. The product consists of two types of material that held together with foundry process. Grinding roll has two kinds of different material properties, outer grinding roll should be hard because it would destroy the mine or rock with material hardness at 9.3 mohs. The inside of the grinding roll should be soft,  for machining process , and also for dampen the vibration caused by the grinding process. In use, the outer layer of the grinding roll will be thinned. The purpose of this study to fix the beam Ni-Hard 1 by coating using a material Ni-Hard 1 with variable temperature liquid interface. The methodology of this study is the beam of Ni-Hard 1 to be coated (called die blank) is heated by the flow of liquid metal Ni Hard1. This process is called flushing. The volume of flushing fluid is accommodated at the disposal basin. The design, which has been determined, simulated using software (solidcast 8.2)  to determine the temperature of interface, and then carried out experiments in the workshop.The bond was analyzed by testing the microstructure, composition, and hardness. Results from this study is the technology to coat Ni-Hard 1 with material Ni-Hard 1 that bonding occurs at the surface. Results of research showed that surface fixing with gravity casting method can be applied at Grinding roll, with the temperature variable interface that must be achieved between 887 ° C – 1198 ° C, flushing time between 10-20 seconds, with a pouring temperature of 1438 ° C – 1468 ° C.